Implikasi Kebijakan Pemekaran Desa terhadap Redistribusi Aset dan Penetapan Administrasif Pemerintahan - Mahruddin Mahruddin (Al-'Adl, 2017)
This study aims to analyze and describe the problems that became implications reallocation of village redistribution of assets and the establishment of government administrative villages in the district Talaga Raya. Focus on research excursions before and after the division of the village. By using descriptive and case study approach, the results showed that the division of the village in the district Talaga Raya has been implicated in the development of infrastructure, of which the number of places of worship which had amounted to only 5 units, now has increased to 8 units. Likewise, the highway, from seven villages in the district have done Talaga highway pavement and concrete. However, of the implications unisex other implications that accompany the expansion is a conflict between some of the elements in the districts of the assets associated with the claim means of taps. While the results penulusuran writer associated with the administrative boundaries of the village administration was no problem, because the local government took the initiative before the expansion is done, the boundaries of the village settled first. By him that splitting the village in the district Talaga Raya Central Buton regency positive impact on the division more than the negative impact due to the addition of assets.